Indeks Kemerataan dan Dominansi Gastropoda di Perairan Pesisir Pantai Moodulio Kabupaten Bone Bolango Provinsi Gorontalo - Windi Deptianingsih Asama; Miftahul Khair Kadim; Sitti Nursinar; Sandrianto Djunaidi (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2025)
Indonesia's marine biological diversity is exceptionally rich, encompassing all existing phyla. Among them, the class Gastropoda represents the largest group within the Phylum Mollusca. Organisms inhabiting hard substrates in intertidal zones exhibit remarkable adaptability to dynamic conditions. Gastropods, in particular, demonstrate a high capacity for adaptation, enabling their survival across various habitats. The level of gastropod species diversity in a given aquatic environment is influenced by several factors, including physical environmental conditions. This study investigates the impact of environmental parameters on the evenness and dominance of gastropods, as well as the effects of environmental changes on these community characteristics. Sampling was conducted at three stations along the coastal area of Bone Bolango Regency. An observational procedure employing a census method was used for sample collection, and purposive sampling determined the sampling points based on specific criteria. Gastropod specimens were collected using a hand-picking technique within a 150 m² transect area, observing the entire station's hard substrate. Water quality data were subsequently analyzed using a pollution index. A total of 422 gastropod individuals were recorded across all stations, representing eight families: Conidae, Cypraeidae, Muricidae, Turbinidae, Neritidae, Strombidae, Tegulidae, and Turbinellidae. Nineteen species were identified from the three research locations. The diversity indices calculated for the three locations are as follows: The Shannon-Wiener diversity index (H′) showed values less than four, indicating moderate diversity. The Simpson's dominance index (D) had values close to one, suggesting a high level of dominance. The Pielou's evenness index (J′) approached one, indicating high evenness within the gastropod community.